Tim dan Organisasi Pembelajar - Raharso, Sri; Amalia, Sholihati (Jurnal Administrasi Bisnis, 2011)
Organization landscape that growing more competitive require organizationto change self individually work-based becomes team setting. Team-basedorganizations is solution for getting the superordinate competitive ability. Basicallyteam potencies can empowered to produce high performance organization. Inother hand, with existence of team, then organization already a step goes forwardto transform become learning organization. This Organization is believed as theorganization structure that can produce continuous innovation.Keywords: team, competitiveness, learning organization